Stir casting process for manufacture of Al-SiC composites - Soltani, Shahin; Azari Khosroshahi, Rasoul; Taherzadeh Mousavian, Reza; Jiang, Zheng-Yi; Fadavi Boostani, Alireza; Brabazon, Dermot (Rare metals, 2017)
Stir casting is an economical process for the fabrication of aluminum matrix composites. There are many parameters in this process, which affect the final microstructure and mechanical properties of the compos- ites. In this study, micron-sized SiC particles were used as reinforcement to fabricate A1-3 wt% SiC composites at two casting temperatures （680 and 850 ℃） and stirring periods （2 and 6 min）. Factors of reaction at matrix/ceramic interface, porosity, ceramic incorporation, and agglomera- tion of the particles were evaluated by scanning electron microscope （SEM） and high-resolution transition electron microscope （HRTEM） studies. From microstructural char- acterizations, it is concluded that the shorter stirring period is required for ceramic incorporation to achieve metal/ce- ramic bonding at the interface. The higher stirring tem- perature （850 ℃） also leads to improved ceramic incorporation. In some cases, shrinkage porosity and intensive formation of A14C3 at the metal/ceramic interface are also observed. Finally, the mechanical properties of the composites were evaluated, and their relation with the corresponding microstructure and processing parameters of the composites was discussed.